Mengantisipasi Lawan Diskursif Islam-Indonesia - Siti Qomala Khayato (Proceedings of Annual Conference for Muslim Scholars, 2018)
This article will explore how radical Muslim in Indonesia renewed and reframed their approaches to backlash government ideological discourse, how radical Muslim built new rapprochement to the populist Moslem lives, trough social media campaign and propaganda, and also how the ways to solve it in order to Indonesian-Islamic identity still adjusted as common models in daily life, using contested hegemony discourse which was conducted by Antonio Gramsci. In sum, this article promotes what writer calls as educating Islamic moderate official-knowledge as citizenship values, trough whole aspects of Muslim lives. The official-knowledge which offers: how to defend the radicalism discourse, how to differ the axiomatic indoctrination and human inquiring of Islamic teaching, and how to rebuild progressive moderate-Muslim as stance which never changing